IMPLEMENTASI KEBIJAKAN PENGHAPUSAN SANKSI ADMINISTRATIF KEPADA WAJIB PAJAK SEBAGAI DAMPAK PENYEBARAN WABAH CORONA VIRUS DISEASE 2019 DI KABUPATEN SUMEDANG - Suherman; Dhalfi Luthfi Prianata; Lurry Amelia Utamy; Muhamad Ramdhan Rizali; Renzi Melyana Ayunda Sari; Sulthan Ariq Fikhriyadi (Sekolah Tinggi Ilmu Administrasi Sebelas April Sumedang, 2021)
This research aims to analyze the implementation of the regent regulation number 87 of 2020 in Regional Revenue Management Agency of Sumedang when it is affected by the COVID-19 pandemic. The method that we used in this research is the qualitative research method and set the variable we observed is the policy implementation. The sampling technique that we used is the purposive sampling that considers some argument based on the data. The sources of the data we observed are the chief of organization, assistant of general position, chief of controlling and monitoring. On analyzing the data we have observed, we used Miles and Huberman’s Model having these several steps: data reduction, data visualization, conclusion drawing/verification, and triangulation. Based on the interview and data analysis, we concluded that the implementation of the regent regulation number 87 of 2020 is statistically well performed as we consider the constructing process, implementation, and participation. Some obstacles on implementing this regent regulation are lack of knowledge of citizen about this regent regulation also lack place of taxes payment. Some strategies on dealing with these obstacles are increasing the campaign of the regent regulation through social media and direct helping of busy citizen on paying the taxes. In this research, we also provide several suggestions i.e. adding several payment access, campaigning citizen on paying taxes on-time, and also accepting some constructive suggestions submitted by citizen.